Medical cannabis education among healthcare trainees: A scoping review - Yuval Zolotov; Samer Metri; Emily Calabria; Mikhail Kogan (Elsevier, 2021)
Objectives: It has been previously demonstrated that healthcare professionals would like additional education on medical cannabis. However, there has not yet been a review of the status of medical cannabis curriculum for medical and allied healthcare trainees worldwide, even though future healthcare workers will be placed on the forefront of patient care and must be prepared to counsel patients. This study was designed to address this gap in knowledge. Design: A search syntax was generated and databases PubMed, ERIC, CINAHL, and Web of Science were searched for relevant articles. A grey literature search of Google Scholar, MedEd, Medline, and the Proquest Dissertations and Theses section was also performed. All titles and abstracts were screened. Selected articles were subsequently screened using predetermined inclusion and exclusion criteria. Results: Allied healthcare trainees lacked sufficient knowledge about medical cannabis and did not feel prepared to counsel patients on this subject. Additionally, they expressed a growing interest in medical cannabis and would like more standardized education on the topic. Finally, faculty and deans in various institutions agreed on the need to educate students on the subject, and aimed to implement courses on medical cannabis or expand their existing curricula. Conclusions: While the medical cannabis landscape is developing, medical and allied health students are not properly educated and knowledgeable on this emerging field of clinical care. The findings suggest that the implementation of competencies-based curricula on medical cannabis is essential for medical and allied healthcare trainees to have the appropriate level of knowledge to counsel and educate their patients.